SELEKSI DAN PEROLEHAN GENETIK PADA UJI KETURUNAN GENERASI KEDUA KAYUPUTIH (Melaleuca cajuputi subsp. cajuputi) DI GUNUNGKIDUL - Sumardi Sumardi; Noor Khomsah Kartikawati; Prastyono Prastyono; Anto Rimbawanto (Jurnal Pemuliaan Tanaman Hutan, 2018)
Breeding for cajuput in Indonesia has moved into advanced generation breeding cycle through establishing second-generation progeny trial. A series of selection would be practiced in the trial before converting into a seedling seed orchard to produce genetically improved seed. In this study, a series of selection, followed by prediction of genetic gain will be observed in the second-generation progeny trial of cajuput established at Gunungkidul. The trial was laid out in randomized complete block design (RCBD), 65 families, three tree-plot, four replications, and spacing of 3 × 1,5 meter. Measurement was conducted on height and diameter at 2 years age. In the trial, within-plot selection has been practiced phenotypicaly by retaining one of the best tree out of the three tree within each plot. Succesive family selection was then simulated from the result of within-plot selection. Results of study showed that estimates of heritabily for diameter were higher than that for height. Genetic and phenotypic correlation between the two traits was moderate at around 0.57. Within-plot selection practiced in the trial resulted positive selection differential for all measured traits. Diameter showed higher coefficient weight of selection (0.4280) than height (0.0406) which indicates that the practiced within-plot selection was more imposed for diameter than that for height. Genetic gain from within-plot selection calculated using selection index were 20.76% for diameter and 12.73% for height. Simulated family selection using the same coefficient weight as within-plot selection resulted lower genetic gain at around 12.26% and 7.52% for diameter and height, respectivelly.